Pengembangan Budaya Religius dalam Meningkatkan Mutu Pendidikan - Fathurrohman, Muhammad (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) UIN Sayyid Ali Rahmatullah Tulungagung, 2016)
Education quality will be reached, if backed up by all organized education component with every consideration. Severally that component is input, process, and output, and it needs to get support utterly of side that have essential role in education institute. But one thing that as focus in here is all this time education quality be assessed with learned achievement, output that accepted at superior college, etcetera, better that thing added by religious point indicators that internalizated in self educative participant. Since religious value internalizated one in self educative participant, although participant is taught that have sky-high achievement, on eventually wills be new Gayus Tambunan. Leave from that thing, therefore so urgent to education institute, notably education intermediates for internalizate to assess religiouses into self educative participant by use of inuring via cultural religious.